Cervical length in prediction of preterm birth after laser surgery for twin–twin transfusion syndrome. (February 2015) - Papanna, R.; Mann, L. K.; Baschat, A. A.; Bebbington, M. W.; Khalek, N.; Johnson, A.; Snowise, S.; Moise, K. J.
ABSTRACT Objectives To determine the risk factors for spontaneous preterm delivery (PTD) or preterm prelabor rupture of membranes (PPROM) at < 34 weeks' gestation after fetoscopic laser surgery for twin–twin transfusion syndrome and to identify the optimal threshold for preoperative cervical length (CL) that indicates a high risk for spontaneous PTD. Methods This was a secondary analysis of data prospectively collected from 449 patients at three fetal centers. CL measurements were obtained by preoperative transvaginal ultrasound, at a gestational age of 16–26 weeks. The risk factors associated with spontaneous PTD before 34 weeks' gestation were determined using multivariable logistic regression analysis. We excluded patients with dual fetal demise and those with maternal or fetal indications for delivery without PPROM (n = 63). The optimal threshold for cervical length to predict spontaneous PTD before 34 weeks was determined using a receiver–operating characteristics (ROC) curve and Youden index. Additionally, the CL threshold for spontaneous PTD at 2‐week intervals between 24 and 34 weeks was determined. Results Spontaneous PTD before 34 weeks occurred in 206 (53.4%) of the included patients. Only the preoperative CL was significantly associated with spontaneous PTD. The preoperative CL was normally distributed with a mean of 37.6 ± 10.3 mm (range, 5–66 mm). Maternal age and parity were positively associated, and gestational age at procedure and anterior placenta were negatively associated, with CL on multivariable linear regression analysis. The area under the ROC curve for predicting spontaneous PTD with CL measurements was 0.61 (P = 0.02) and the optimal threshold was 28 mm with a Youden index of 0.19 (sensitivity and specificity of 92% and 27%, respectively). A CL measurement of < 28 mm increased the risk of spontaneous PTD for all gestational age thresholds. Conclusions Spontaneous PTD at < 34 weeks' gestation is associated with a preoperative CL of < 28 mm. Preventive strategies should focus on this high‐risk group. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.